(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The long-standing energy supply issues faced in Nigeria and especially in areas such as Anambra State where power cuts are the main causes of poor socio-economic development requires the use of viable domestic solutions. The paper evaluates the piezoelectric energy harvesting of naturally occurring quartz and tourmaline in Abagana and Ukpo areas of the state of Anambra. To be ethical, 50 samples (25 samples of quartz and 25 samples of tourmaline) were visited in five artisanal mining sites that were chosen purposely and with the help of miners. Measurement of longitudinal piezoelectric coefficient (d 3 ) at Nnamdi Azikiwe University was done with measuring Berlincourt meter and voltage pressure within conditions of simulated mechanical stress that determines footsteps and machinery vibration common in local markets and industries across the region. The mean d 33 of 2.15 + 0.18 pC/NUnder compressive load of 500 N is 2 Hz yielded quantitative results as determined by statistical software giving means of 2.15 0.18 pC/N in quartz and 3.82 0.45 pC/N in tourmaline, with average open-circuit voltages of 18.7 mV and 24.6 mV, respectively. A prototype cantilever with processed samples of tourmaline generated a maximum of 12 μW in a simulated foot traffic, and was shown to be viable in making low-power devices. The abundance of materials and challenges of extraction and processing were highlighted in a qualitative study on 10 miners (80% male), with a mean age of 44 years, and 10 owners of small and medium enterprises (70% male), whose average age was 39 years. The scientific standards, such as consent of the community and sustainability, were maintained. Results verify that tourmaline is the best of natural minerals to work with in the context of generating decentralized energy in off-grids. This helps to enhance the lead free piezoelectric research, as part of environmental sustainability and renewable energy targets of Nigeria and suggests that policy reinforcement should be through the refinement of local materials and local based projects.